Penerapan Bridging Exercise Terhadap Keseimbangan Tubuh pada Pasien CVD Non Hemoragik di Ruang Rawat Inap (VitaMedica : Jurnal Rumpun Kesehatan Umum, 2026)
Non-hemorrhagic cerebrovascular disease (CVD) results from blood flow obstruction in the brain due to thrombus or embolus formation, often leading to balance disorders that affect standing and walking. This loss of motor function increases the risk of falls and fractures, which are major complications. Additionally, reduced physical activity can lead to depression. Active exercise has been shown to improve motor function in CVD patients, with nurses playing a key role in supporting these exercises. One effective intervention is the bridging exercise (BE), used for lumbopelvic stabilization, which enhances muscle strength and coordination. BE is particularly beneficial for improving balance in post-CVD patients with hemiplegia. This case study examines the effects of evidence-based bridging exercise (EBP) on balance in three hospitalized non-hemorrhagic CVD patients. Over eight 15-minute sessions, balance was assessed using the Berg Balance Scale (BBS). All patients showed significant balance improvement, with an average BBS score increase of 40 points. These results highlight the effectiveness of non-pharmacological bridging exercises in enhancing balance in CVD patients and recommend BE as a routine therapy to continue at home after discharge.